Community structure and collapses in multichannel food webs: Role of consumer body sizes and mesohabitat productivities - Dijoux, Samuel; Boukal, David S (Ecology letters, 2021)
Multichannel food webs are shaped by the ability of apex predators to link asymmetric energy flows in mesohabitats differing in productivity and community traits. While body size is a fundamental trait underlying life histories and demography, its implications for structuring multichannel food webs are unexplored. To fill this gap, we develop a model that links population responses to predation, and resource availability to community-level patterns, using a tri-trophic food web model with two populations of intermediate consumers and a size-selective top predator. We show that asymmetries in mesohabitat productivities and consumer body sizes drive food web structure, merging previously separate theory on apparent competition and emergent Allee effects (i.e. abrupt population collapses) of top predators. Our results yield theoretical support for empirically observed stability of asymmetric multichannel food webs and discover three novel types of emergent Allee effects involving intermediate consumers, multiple populations or multiple alternative stable states.
Keywords: predátorské chování; velikost těla; potravní řetězec; Predatory Behavior; fenotyp; Phenotype; Animals; Apparent competition; emergent Allee effects; limiting similarity; Body Size; size-dependent predation; alternative stable states; zvířata; Food Chain